2017
DOI: 10.1021/acssuschemeng.7b00630
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Twin Screw Extrusion and Chemical Pretreatment as an Energy-Efficient Method for the Production of Nanofibrillated Cellulose at High Solid Content

Abstract: Production of nanofibrillated cellulose (CNF) has gained increasing attention during the last decades with its recent industrialization, but such a process consumes still too high of an amount of energy. Here, cellulose nanofibrils at high solid content (20−25 wt %) and consuming 60% less energy compared to conventional processes were produced from enzymatic and TEMPO-oxidized cellulose fibers thanks to a twin screw extruder equipped with kneading disks and fully flighted conveying screws. The morphology and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 57 publications
5
99
0
Order By: Relevance
“…In addition, low viscosity might enable the production of CWNFs with a high solid content, for example, using a twin-screw extruder. 52 TEM analysis showed that cationic wood disintegrated into individual nanobers with a width of approximately 5 nm (Table 1 and Fig. 2).…”
Section: Nanobrillation Of Cationic Woodmentioning
confidence: 99%
“…In addition, low viscosity might enable the production of CWNFs with a high solid content, for example, using a twin-screw extruder. 52 TEM analysis showed that cationic wood disintegrated into individual nanobers with a width of approximately 5 nm (Table 1 and Fig. 2).…”
Section: Nanobrillation Of Cationic Woodmentioning
confidence: 99%
“…In the particular case of CNFs production, the enzymatic hydrolysis is commonly followed by a mechanical step of fibrillation, such as homogenization [ 38 , 44 ], microfluidization [ 49 , 50 ], extrusion [ 25 , 51 ], and sonication [ 27 , 52 ], among others. Few studies have also reported no mechanical treatment step after hydrolysis [ 12 , 53 , 54 , 55 ], hence totally relying on the enzymes to produce the nanofibers.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
“…While these benefits from enzymes are consensual, there is a clear lack of accurate estimations of the putative energetic savings introduced by enzymes. As pointed out by Rol et al [ 51 ], this comparison should be carefully conducted since distinct extraction processes may produce NC particles with different modification rates and dimensions. A recent study by Espinosa et al [ 25 ], employing an extrusion process after hydrolysis, reported a reduction of 37% of the energy consumption.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various methods have been adopted for the preparation of CNCs, in which mechanical and hydrolyzed methods are the two main kinds. The mechanical methods include high‐pressure homogenization, grinding, sonication, and so forth, whose main drawback is high energy consumption . Although the chemical hydrolyzed method has advantages of high reaction efficiency and CNC yield, it has the disadvantages of high chemical additions and environmental pollution at the same time .…”
Section: Introductionmentioning
confidence: 99%